Membaca Kebohongan Media Amerika - Sobur, Alex (Mediator, 2006)
According to Jerry Gray, author of “Media Sins in US” (2006), media were responsible to represent a huge amount of biased facts. For example, US media have depicted Saddam Hussein, Iraqi leader, as the most dangerous threat for American. A high diplomatic leader, John Brady Keisling, agreed with Gray’s statement. He reported saying that intelligent information had being distorted systematically to manipulate Americans opinion. This article tried to dig relation between media biased and the main source of media power in the hands of media owner. More than half of media moguls rooted to a Jewish family, and they were capable to construct and circulating news which served best for their sake.